Correlation of Sentul Chicken Body Weight at DOC age of 1, 2 and 3 Months - L. H. M. Gultom; Gushairiyanto Gushairiyanto; Depison Depison (Jurnal Sain Peternakan Indonesia, 2021)
The purpose of this study was to determine the correlation between body weight and body weight gain of Sentul chickens aged DOC, 1, 2, and 3 months.  The research materials were Sentul and Merawang chicken. This research method was an experimental method with a sample of 41 males and 41 females from each breed. The data collected includes; body weight and body weight gain of DOC-3 months old. The data that have been collected were analyzed using the t-test of average differences (t-test), the relationship between body weights was analyzed using the correlation test. Based on the results and discussion, it can be concluded that the body weights of male and female of Sentul chicken aged DOC-2 months were not significantly different (P>0.05), but significantly different (P<0.05) at the age of 3 months. The highest body weight gain was at 1-2 months in both males and females. The highest correlation between body weights for a certain age is between 1-2 months so that 1-month body weight is a good bodyweight for selection based on body weight.